2018
DOI: 10.1186/s40981-018-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intravenous anesthetics on QT interval during anesthetic induction with desflurane

Abstract: Introduction: This study aimed to determine the effects of the interaction between intravenous anesthetics and desflurane on the QT interval. Methods: Fifty patients who underwent lumbar spine surgery were included. The patients received 3 μg/kg fentanyl and were randomly divided into two groups: group P patients received 1.5 mg/kg propofol and group T patients received 5 mg/kg thiamylal 2 min after fentanyl injection. All patients received rocuronium and desflurane (6% inhaled concentration) after loss of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…QTD, the difference between the maximum and minimum QT intervals, is considered an index of left ventricular repolarization inhomogeneity [26]. Increased QTD or QTcD is a sign of heterogeneous repolarization and possible arrhythmogenic re-entry [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTD, the difference between the maximum and minimum QT intervals, is considered an index of left ventricular repolarization inhomogeneity [26]. Increased QTD or QTcD is a sign of heterogeneous repolarization and possible arrhythmogenic re-entry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although inhalational anesthetics significantly increased the QTc interval, no dysrhythmia was reported during anesthesia with inhalational anesthetics in the studies included this meta-analysis. Some RCTs [17,26,[30][31][32][33] reported that transient dysrhythmias, such as supraventricular arrhythmia, ventricular arrhythmias, and idioventricular rhythm, were detected in the treatment of anesthetics including propofol, thiamylal, thiopentone, sevoflurane, isoflurane, and halothane, but no intergroup differences were reported. This might have occurred because all the RCTs investigated adult patients with normal QTc interval and no cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%